Evaluasi Perhitungan Harga Pokok Penjualan Laundry di Perusahaan Laundry Skala Besar - Nur, Muhammad Akbar; Fatima, Eliza (E-Jurnal Akuntansi; Vol 34 No 8 (2024), 2025)
This research aims to find out the calculation formula of the laundry Cost of Sales (COS) that PT.X applied and evaluate it using the activity-based costing (ABC) method. The object of this research is a large-scale laundry company that provides quality laundry services and free delivery to various clients in the Greater Jakarta area (Jabodetabek). The method used in this research is qualitative with a case study approach. The research results show that the current COS calculation per kg of hotel laundry is 40,43% greater (overcosting) than the ABC method. Meanwhile, COS per kg of guest & uniform laundry is 20,74% smaller (undercosting) than the ABC method. Other results show that the gross profit margin for both laundries is 5,64% greater if PT.X uses the ABC method. The large number of indirect costs and there are the differences in machine use and manual handling each of laundry indicate that activity-based costing needs to be considered by company management to obtain more appropriate cost product information. Keywords: activity-based costing; cost of sales (COA); large-scale laundry company; profitability